The financial sustainability of publicly-traded state-owned enterprises in an emerging market - Al Kharusi, Sami; Murthy, Sree Rama (Opción, 2019)
This paper discusses the financial sustainability of 19 publicly traded enterprises with more than 5% state ownership and listed on Oman’s Muscat Securities Market. To examine the enterprises’ financial sustainability, simulations using key financial ratios were performed, which revealed that at least four manufacturing firms and two banks will likely face financial instability and may become financially unsustainable. In conclusion, we also recommend conducting scenario analysis using likely macroeconomic scenarios and their impact on the financial stability of predominantly state-owned publicly traded listed companies.